COMMUNITY-BASED EDUCATION ON HEALTHY SNACK CHOICES TO PREVENT EARLY DIABETES AMONG STUDENTS OF AL-HIKAM ISLAMIC BOARDING SCHOOL, BANGKALAN - Ardyarini Dyah Savitri; Lea Maera Shanty; Effendi; Viera Nu’riza Pratiwi; Akbar Reza Muhammad; Ahla Nurul Istiqomah (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Diabetes mellitus (DM) is one of the global health threats, and in Indonesia, the prevalence of DM continues to increase every year. The risk factors for DM that are currently challenging are an unbalanced lifestyle, including the habit of consuming snacks high in sugar. Situation analysis shows that students at Islamic boarding schools have limited knowledge about diabetes and often enjoy snacks without considering their sugar content. On the other hand, sweet potatoes grow abundantly in the environment of the Al-Hikam Bangkalan Islamic boarding school. Sweet potatoes are known to have a low glycemic index and are high in fiber, making them a healthy snack alternative to prevent the risk of diabetes. The purpose of this community service is to introduce healthy snacks for diabetes to prevent the early risk of diabetes among students at PP. Al-Hikam Bangkalan. This community service used an observational analytical method in processing questionnaire data. Activities included counseling on the dangers of DM and healthy anti-diabetic snacks. The Participants consisted of 51 male and female students at PP. Al-Hikam Bangkalan, which began with a pre-test, continued with the delivery of material, and ended with a post-test as an evaluation. The results of the Wilcoxon signed rank test showed an increase in the knowledge of the participants, with a pre-test average score of 31 and a post-test average score of 64, representing a significant increase (P <0.001). The conclusion is that students were able to understand diabetes mellitus and recognize healthy anti-diabetic snacks after receiving counseling, so it is hoped that students can maintain a balanced diet and make healthy snacks as an alternative to snacks so that they can prevent diabetes early on.